The impact of the state´s urban planning powers in the real estate sector and its repercussions on fundamental right - Cerrón Valdivia, José Antonio (2023)
In this article, the author studies the delay or slowness of the procedures for the granting of urban and building licenses, which is mainly due to the lack of knowledge of the applicable regulations and/or the arbitrary or deficient exercise of municipal officials, which in turn results in the demand for greater requirements than those contemplated in the national regulatory framework, the creation of new administrative procedures, among others.The delay of such procedures not only affects real estate projects, but also has an impact on the complementary activities and services necessary for their execution, such as the design, preparation and execution of the projects, the supervision of the works, the hiring and beginning of work by contractors, suppliers of inputs and services, administrators and workers, purchasers of real estate units, among other services and activities that contribute to the country’s economy; as well as affecting property freedoms and recognized fundamental rights.